2017
DOI: 10.1002/jum.14265
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasonography‐Guided Fine Needle Aspiration Can Be Used to Rule Out Malignancy in Autoimmune Pancreatitis Patients

Abstract: Almost all pancreatic cancers can be diagnosed by EUS-FNA. Furthermore, other clinical characteristics of pancreatic cancer undiagnosed by EUS-FNA were different from autoimmune pancreatitis undiagnosed by EUS-FNA. Endoscopic ultrasonography-guided FNA can be used to rule out malignancy in autoimmune pancreatitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…At present, the accurate differential diagnosis of AIP and PC before surgery has become a hot topic for clinicians and scholars. The value of CT examination in the diagnosis and staging of PC has been clinically recognized, and it is regarded as the best imaging method for PC examination (18,19). In recent years, CT has been used increasingly in the differential diagnosis of AIP and PC, and the CT characteristics of the 2 diseases are significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the accurate differential diagnosis of AIP and PC before surgery has become a hot topic for clinicians and scholars. The value of CT examination in the diagnosis and staging of PC has been clinically recognized, and it is regarded as the best imaging method for PC examination (18,19). In recent years, CT has been used increasingly in the differential diagnosis of AIP and PC, and the CT characteristics of the 2 diseases are significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the diagnostic difficulty of AIP by EUS-FNA with the limited sensitivity of 0-19% for pathologically definite diagnosis of LPSP, because EUS-FNA could not provide sufficient tissue samples for histological evaluation [26,27,[33][34][35]. Iwashita et al reported the improved sensitivity of 43% using a 19-gauge FNA needle [29].…”
Section: Discussionmentioning
confidence: 99%
“…Novel needles have been developed with side holes or dedicated tip designs to obtain adequate tissue samples for histological evaluation and are called EUS-guided fine needle biopsy (EUS-FNB) needles [15][16][17][18][19][20][21][22][23][24]. Recently, the diagnostic yield of EUS-FNA for AIP has been reported [25][26][27][28][29][30][31][32][33][34][35], and EUS-FNB is expected to provide the better yield [25,36].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, some authors have proposed FNA to rule out malignancy. A retrospective study on FNA (18-, 22-, and 25-gauge needles) in 40 AIP patients reported a histological diagnosis of AIP only in six patients (15%), with a single patient (2.5%) misdiagnosed with acinar cell carcinoma [ 8 ]. Among the remaining AIP patients without a histological diagnosis, the authors found significant differences in the radiological features and Ca19.9 levels compared with those with pancreatic cancer and inconclusive FNA.…”
Section: Fine-needle Aspiration (Fna) and Fine-needle Biopsy (Fnb)mentioning
confidence: 99%